(untitled) (Journal of Economic Additions, 2025)
This research paper aimed to test the impact of capital structure on the financial performance of a group of industrial enterprises in Tlemcen Province during the period from 2018 to 2022. The study employed panel data analysis using the Generalized Method of Moments (GMM) to test the effect of independent variables on financial performance. The findings revealed an inverse relationship between capital structure, measured by the total debt ratio, and return on assets. A non-significant negative impact was observed when long-term debt was utilized. Furthermore, the firm’s activity had a positive effect on financial performance, while the tangibility had an insignificant negative effect on return on assets. Keywords: capital structure; financial performance; total debt ratio; long term debt ratio; return on assets. Jel Classification Codes : G32, L25, C33.